(3GdJHjGf aj Yde GdHjGf GdeWdY Ydi EYLGR GdbQBfs - (3YHO GdhGMO Hf YHO GdcQje Hf Nda GdCfUGQj GdRedcGfj, CHh GdecGQe, ceGd GdOjf, hjbGd dg GHf NWjH RedcG,J (B651 (3g` s ((3YHO dGdg Hf eMeO Hf jhSa Hf ZjGK GdOjf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfWb CdSfI GdCbdGe HEMcGe GdCMcGe , haJb CZTjI GdCaFOI HEagGe GdCagGe , hChOY NRGFf GdUOb LhGgQ GdcdGe s
(3BNQgG (B:s
(3hYdeJ ef Cjf jLJfH GdNWC , hcja jbJHS GdUhGH hGdMeO ddg QH GdYGdejf Je cJGH GdJHjGf GdeWdY Ydi EYLGR GdbQBf s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JYdjbGJs
(3hcJHJ GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs